Pregunta
upstudy study bank question image url

10. Find the value of \( k \) for which the equation \( (k-2) x^{2}+x(2 k+1)+k=0 \) has equal roots.

Ask by Curry Hills. in Ireland
Nov 10,2024

Solución de inteligencia artificial de Upstudy

Respuesta verificada por el tutor

Responder

The value of \( k \) is \( -\frac{1}{12} \).

Solución

To determine the value of \( k \) for which the quadratic equation \[ (k-2)x^2 + (2k+1)x + k = 0 \] has equal roots, we need to use the condition for equal roots in a quadratic equation. A quadratic equation \( ax^2 + bx + c = 0 \) has equal roots if its discriminant \( D \) is zero, where the discriminant is given by \[ D = b^2 - 4ac. \] In our case, we identify the coefficients as follows: - \( a = k - 2 \) - \( b = 2k + 1 \) - \( c = k \) Now, we can compute the discriminant: \[ D = (2k + 1)^2 - 4(k - 2)(k). \] Expanding \( D \): 1. Calculate \( (2k + 1)^2 \): \[ (2k + 1)^2 = 4k^2 + 4k + 1. \] 2. Calculate \( 4(k - 2)(k) \): \[ 4(k - 2)(k) = 4(k^2 - 2k) = 4k^2 - 8k. \] Now, substituting these into the discriminant: \[ D = 4k^2 + 4k + 1 - (4k^2 - 8k). \] Simplifying this expression: \[ D = 4k^2 + 4k + 1 - 4k^2 + 8k = 12k + 1. \] To find the value of \( k \) for which the roots are equal, we set the discriminant equal to zero: \[ 12k + 1 = 0. \] Solving for \( k \): \[ 12k = -1 \quad \Rightarrow \quad k = -\frac{1}{12}. \] Thus, the value of \( k \) for which the equation has equal roots is \[ \boxed{-\frac{1}{12}}. \]

Respondido por UpStudy AI y revisado por un tutor profesional

error msg
Explicar
Simplifique esta solución

Beyond the Answer

To find the value of \( k \) for which the quadratic equation \( (k-2)x^2 + (2k+1)x + k = 0 \) has equal roots, we use the condition that the discriminant must be zero. First, we calculate the discriminant \( D \) of the quadratic equation \( ax^2 + bx + c = 0 \): \[ D = b^2 - 4ac \] In this case, \( a = k - 2 \), \( b = 2k + 1 \), and \( c = k \). Plugging these into the discriminant formula gives: \[ D = (2k + 1)^2 - 4(k - 2)(k) \] Now, we simplify this expression: \[ D = (2k + 1)^2 - 4(k^2 - 2k) \] Calculating \( (2k + 1)^2 \): \[ (2k + 1)^2 = 4k^2 + 4k + 1 \] Next, calculate \( -4(k^2 - 2k) \): \[ -4(k^2 - 2k) = -4k^2 + 8k \] Now, we combine both parts for \( D \): \[ D = (4k^2 + 4k + 1) - (4k^2 - 8k) \] \[ D = 4k^2 + 4k + 1 - 4k^2 + 8k \] \[ D = 12k + 1 \] For the quadratic to have equal roots, we need to set the discriminant to zero: \[ 12k + 1 = 0 \] Solving for \( k \): \[ 12k = -1 \] \[ k = -\frac{1}{12} \] Thus, the value of \( k \) for which the equation has equal roots is \[ \boxed{-\frac{1}{12}}. \]

preguntas relacionadas

Latest Algebra Questions

¡Prueba Premium ahora!
¡Prueba Premium y hazle a Thoth AI preguntas de matemáticas ilimitadas ahora!
Quizas mas tarde Hazte Premium
Estudiar puede ser una verdadera lucha
¿Por qué no estudiarlo en UpStudy?
Seleccione su plan a continuación
Prima

Puedes disfrutar

Empieza ahora
  • Explicaciones paso a paso
  • Tutores expertos en vivo 24/7
  • Número ilimitado de preguntas
  • Sin interrupciones
  • Acceso completo a Respuesta y Solución
  • Acceso completo al chat de PDF, al chat de UpStudy y al chat de navegación
Básico

Totalmente gratis pero limitado

  • Solución limitada
Bienvenido a ¡Estudia ahora!
Inicie sesión para continuar con el recorrido de Thoth AI Chat
Continuar con correo electrónico
O continuar con
Al hacer clic en "Iniciar sesión", acepta nuestros términos y condiciones. Términos de Uso & Política de privacidad